(untitled) - Bjarne Stroustrup (Massachusetts, 1997)
This book introduces standard C++ and the key programming and design techniques supported by C++. It offers something to even the most experienced C++ programmer. This book presents every major C++ language feature and the standard library. It demonstrates key techniques that make C++ effective and teaches the fundamental concepts necessary for mastery. A companion, The Annotated C++ Language Standard, presents the complete language definition together with annotations to make it more comprehensive
Keywords: C++ ( computer programming language )